The Journey of Exceptional Educational Leaders in Higher Education Institutions in Region III - Ayro, Eufemia C.; Cruz-Vidal, Michaela Jennarine DL.; Eugenio, Arnold C.; Lazaro, Cherrylyn G. (Future Science / FSH-PH Publications, 2025)
This study concentrated on the journey of exceptional education lead-ers in higher education institutions in Region III. This study used the qualitative descriptive, specifically the case study method. This study described and explored the lived experiences of exceptional education leaders. Case analysis, unstructured interviews and observations were used to gather data from the participants. The participants of the study belonged in late adulthood, female, finished their doctorate degree in education and in other disciplines, holding academic posi-tion of Professor 7 and was previously appointed as College of Educa-tion Dean. The educational background of the participants manifested that they were shaped with the learnings acquired in their academic journey. The knowledge-based, skills and abilities to perform effective-ly in their demanding roles demonstrated that they were capable to handle various responsibilities, and many challenges evolve within their workplace. They were affiliated to various recognized organiza-tion to established network and linkages. In terms of leadership quali-ties, most of them said that they used servant leadership; they were people oriented and innovative. Moreover, most of them stated that the qualities of a good academic leaders were knowledgeable, motivator, responsible and have good relationship with people. The participants had strong interpersonal relationship with their colleagues because they were team players, active listeners and flexible leaders. Moreo-ver, their short- and long-term vision is to sustain and maintain their accreditation status through compliance to the accreditation indica-tors that attest their educational quality in pursuit of academic excel-lence. In terms of best practices in curriculum and instruction, the participants claimed that their curriculum and program of studies meets the requirements and standards of the Commission on Higher Education, Professional Regulations Commission, Professional Organi-zation or Societies and other related agencies which were reflective to national and regional goals, and institutional vision and mission, and provide for the development of various competencies. Similarly, all participants stated that they ad-here with the National Higher Education Research Agenda and Na-tional Unified Health Research Agenda in the formulation of their In-stitutional Research Agenda which were aligned with priority thrust of regional and national priorities of government agencies and private sectors. All participants stated that they adhere to the importance of extending their services to communities outside their campuses. Spe-cifically, the administration, faculty and students are involved in the identification, planning and implementation of extension programs of the institutions. An office that specifically oversees the operations of the extension services is present in the study, of higher education in-stitutions. These distinct offices ensure that a variety of clientele ben-efit from well designed and disseminated programs owing to the adoption of a system that makes those programs sustainable, were regularly monitored and evaluated. Finally, the participants encoun-tered problems and challenges related to the “knowledge quadrant” such as curriculum and instruction, research, community extension and other administrative support.